Screening for vancomycin-resistant enterococci using stools sent for clostridium difficile cytotoxin assay is effective: Results of a survey of 300 patients in a large Singapore teaching hospital - Tay, J.K.X. (2015)
Annals of the Academy of Medicine Singapore